The TRIPS compulsory licensing regime and access to medicine: current challenges and future prospects - Igbokwe, Ezinne Mirian (2021)
The disproportionate application of public health challenges in low-income countries (LICs) poses a significant threat to the realisation of the right of access to medicine. High price of patented drugs has been linked to this challenge. The exploitation of pharmaceutical patent protection generally and under the TRIPS Agreement, has been identified as empowering pharmaceutical firms to charge supra competitive prices for innovator drugs. Notably, the TRIPS Agreement and national Intellectual Property (IP) legislations are sensitive to the access gap arising from this challenge. Compulsory license flexibility in Article 31bis of the TRIPS Agreement has further been recognised as one of the measures that can induce price reduction of patented drugs. Accordingly, the need to address how patent protection on drugs threatens public health, the realisation of right of access to medicine and the use of compulsory license to facilitate access to medicine, form the motivations and objectives of this thesis. Paragraph 6 objective of the 2001 Council of TRIPS Doha Declaration recognised the effect of patent on price of drugs and the need to promote the effective use of compulsory license by countries with insufficient pharmaceutical manufacturing capacity. Consequently, under determinate circumstances, Article 31bis of the TRIPS Agreement permits the exportation of drugs that are produced under compulsory license to a needing state. Incidentally, Article 31bis effort has been described as ‘unworkable, impracticable and incapable of generating sufficient economies of scale’. This argument has therefore raised a concern that Article 31bis may be unable to satisfy the paragraph 6 objective of the Doha Declaration. Based on the forgoing, this study embarks on the analysis of Article 31bis to determine the practicality towards the paragraph 6 objective. This thesis identifies four major challenges that confront Article 31bis. They are: the procedural requirements of Article 31bis, trade politics, advanced IP trade measures (TRIPS-Plus) in Free Trade Agreements (FTAs), and limited economies of scale. These challenges are respectively categorised as procedural (legal), political, substantive and economic challenges. Based on these challenges, this thesis asked this question: can Article 31bis of the TRIPS Agreement maximize the Doha Declaration’s Paragraph 6 objective, in balance of the patent holder’s right. To answer this question, this study embarks on a legal, socio-legal and interdisciplinary analysis to evaluate the patent mechanism, pharmaceutical patent protection under the TRIPS Agreement, the right of access to medicine, and Article 31bis. Based on the issues emerging from the analysis, the answer to the research question takes the form of an argument. The argument is that, despite the four-fold challenges that contest Article 31bis mechanism, Article 31bis can still exploited in the current state once the economics is right. This thesis argues that even though Article 31bis mechanism problematic, it is capable of satisfying the paragraph 6 objective. Against the backdrop of the right economics for Article 31bis, this study considers a strategic use of Article 31bis in the current state. Consistent with Article 31bis(3) of the TRIPS Agreement, this study argues that a regional approach to compulsory license can produce the right economies of scale for Article 31bis. Illustrating with the existing Regional Economic Communities (RECs) in Africa, this thesis demonstrated how a joint or regional compulsory license can significantly satisfy paragraph 6 objective of the Doha Declaration in balance of the patent holder’s right. Significantly, Article 31bis was analysed as capable of providing legal and economic solutions that can bridge the gap between the right of access to medicine and pharmaceutical patent protection.